PRESCHOOL EDUCATION ABROAD - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Preschool education has an incomparable place in every great country with developed education. Based on the world experience, Uzbekistan also pays great attention to the preschool education system. Preschool education is the basic foundation of general secondary education and higher education. The stronger the foundation, the more beautiful the building will be and will last for many years. In recent years preschool infrastructure and the quality of education in Uzbekistan have been radically reformed and developed. This article describe in detailed the experiences of the preschool education system in the developed countries of America, Britain, and Russia as well as the reforms and innovations in the preschool education system in Asian countries and Uzbekistan.